The Cognitive Evolution from "Plague" to "Infectious Disease" - Xi Gao (Wolters Kluwer Health/LWW, 2020)
According to the Grand Chinese Dictionary, plague is defined to be an acute infectious disease. The Chinese term "infectious disease" is not what it is commonly thought originated from Japanese. The medical nomenclature shift from the traditional "plague" to the modern "infectious disease" is completed by the medical missionaries, Chinese scholars, and the national authority, each utilising different strategies. It is a history of acceptance concerning the concept of "infectious disease" from academia to national level. The conscious use of infectious disease-related thought and terminology by Chinese officials and doctors when studying infectious disease is a scientific modernization towards the understanding of epidemics. In a sense, this evolution of medical knowledge embodies the modernization of infectious disease in China.